An experimental study of color perception among selected elderly Filipino females - Olinares, Jamie Kris Coronel; Quevedo, Ma. Teresa P. (2008.)
The study sought to determine whether elderly Filipino females can accurately perceive primary and secondary colors in the color wheel under natural and artificial lighting during daytime and night-time. The objectives of the study were to find out how these colors were perceived, and if there were any distortions in the color perception of the respondents. Using an experimental research design, color swatches of primary and secondary colors were shown to the respondents under natural and artificial lighting conditions during daytime and night-time. Twenty elderly Filipino females comprised the respondents of the study. They were selected through purposive sampling based on a set criteria: they should be females and "elderly" meaning, they should be at least 60 to 75 years old. Another experiment was also conducted by the researcher to simulate the color perception of the elderly using personally made eyeglass with yellow lenses. Results show that of the twenty respondents, eleven exhibited problems in perceiving the color blue. Out of the eleven, two had problems perceiving the color violet and one had a problem perceiving the color green. Distortion perceived by the eleven respondents include a darkening of the color blue that appeared as blackish, gray-like color, and a darkening of the color violet that appeared as a blackish, red-violet color. In addition, the color green was perceived by one of the eleven respondents as a darker shade of the same color. Results revealed that lighting did not necessarily affect the color perception of the selected elderly respondents. However, the researcher was able to note that all twenty respondents preferred natural lighting for viewing the swatches used for the experiment. All twenty respondents agreed that they or their eyes seemed to be more comfortable in viewing the colors shown to them under natural lighting. These served as the most prevailing finding of the study that generally concur with previous studies and existing literature.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Color vision -- Philippines